Preliminary evaluation of the efficacy of an intervention incorporating precision teaching to train procedural skills among final cycle medical students. (13th February 2017) - Lydon, Sinéad; Burns, Nadine; Healy, Olive; O'Connor, Paul; Reid McDermott, Bronwyn; Byrne, Dara
Abstract : Introduction: A lack of preparedness for practice has been observed among new medical graduates. Simulation technology may offer one means of producing competency. This paper describes the application of a simulation-based intervention incorporating precision teaching (PT), a method of defining target skills, assessing individual progress and guiding instructional decisions, which is used to monitor learning and the development of behavioural fluency in other domains, to procedural skills training. Behavioural fluency refers to accurate and rapid responding that does not deteriorate with time, is resistant to distraction and can be adapted into new, more complex responses. Method: This study used a between-groups design to evaluate the efficacy of a simulation-based intervention incorporating PT for teaching venepuncture among 11 medical students. The intervention consisted of timed learning trials during which participants carried out the skill in pairs and received corrective feedback. Two control groups of 11 untrained medical students and 11 junior doctors were also included in the study. Results: Intervention group participants required an average of five trials and 21.9 min to reach the criterion for fluency. The intervention group demonstrated significantly higher accuracy in venepuncture performance than either control group. Improvements persisted over time, did not deteriorate during distraction, generalised to performance with patients and performance of an untargeted skill also improved. Conclusions: The outcomes of this preliminary study support the application of PT within medical education. The implications of these data for clinical and procedural skills training are explored and suggestions are made for further research.